Panel discussion: what don't we know about confinement? - Alkofer, Reinhard; Pawlowski, Jan M. (Arxiv, 2011)
The participants in this discussion session of the QCHS 9 meeting were each asked the following question: "What would be the most useful piece of information that you could obtain, by whatever means, that would advance your own program, and/or our general understanding of confinement?" This proceedings contains a brief summary of each panel member's contribution to the discussion, provided by the panel members themselves.
das "don´t" ist kurviert geschrieben
Gesehen am 01.12.2017